2023
DOI: 10.1111/gwat.13288
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Groundwater and Spring Water Residence Times near the Coast of Fukushima, Japan

Abstract: The massive Tohoku earthquake, colloquially known as “The 2011 Great East Japan Earthquake,” occurred off the Pacific coast of Japan on March 11, 2011. The coastal area of the Tohoku region was severely affected by the tsunami, and the tsunami also caused severe damage to the Fukushima Daiichi Nuclear Power Plant (FDNPP) releasing a large amount of radioactive material into the atmosphere and environment. Determining the residence time of groundwater is important for evaluating how long radioactive materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Detailed water chemistry analyses in the two reaches clearly showed that the elevated EC in hyporheic water was partially driven by high levels of nitrate. The levels of nitrate observed were high and were comparable with the average levels reported in human-affected groundwater in farmlands and livestock fields in Japan (1.4 to 20 mg/L as NO 3− N; 3.15 to 45 mg/L as nitrate) (Yabusaki, 2010). Globally, human activities, such as urbanization and agriculture, have elevated nitrate levels in water to comparable levels (Drake & Bauder, 2005; Negishi et al, 2019; Su et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…Detailed water chemistry analyses in the two reaches clearly showed that the elevated EC in hyporheic water was partially driven by high levels of nitrate. The levels of nitrate observed were high and were comparable with the average levels reported in human-affected groundwater in farmlands and livestock fields in Japan (1.4 to 20 mg/L as NO 3− N; 3.15 to 45 mg/L as nitrate) (Yabusaki, 2010). Globally, human activities, such as urbanization and agriculture, have elevated nitrate levels in water to comparable levels (Drake & Bauder, 2005; Negishi et al, 2019; Su et al, 2021).…”
Section: Discussionsupporting
confidence: 77%